(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the importance and advantages of using information technologies in teaching the fairy tale genre in primary school reading literacy classes. The article also analyzes audio fairy tales given in current reading literacy textbooks and expresses its views on their role in improving students’ worldview and logical thinking, as well as in developing important life skills.